The progress of man - Pope, Warner S. (My University, 1892)
Introduction: It is natural that we should contemplate the past, the present and the future. The past to note the principles that underlie government and society, so that we may apply them to our present need in promoting the good of man. The present in raising the human race to a higher degree of purity and excellence. The future in providing for the generations to cure by transmitting the benefits we have enjoyed, and to add to the gift the results of our own efforts. It is only by the study of man, as man, intellectually, morally, and physically may we hope to make progress. To do this, we establish schools of learning whose graduates trained to observe in the different fields of knowledge, give us the pearls of priceless value. It is in the ruins of man’s works that we perceive progress, where has spent his energy, stamped indelibly his leading characteristics, on granite or marble that defies time with its corroding agencies. In primitive man, we know his habits by the rude tools he has left behind; we see him clothed in the skins of wild animals, no storing up of food for future wants, surrounded by nature in its original form. He is its child. No restraint to passions which under control stimulate the faculties, and lead the civilization but unchecked sinks the man deeper and deeper into the depths of darkness. Then man is no better than the wild animal that surround his habitation.
Citation: Pope, Warner S. The progress of man. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Human development; Neanderthal; Progress; Anthropology; Theses; Manuscripts (documents)